COVID-19 And Lockdown: Be Logical in Relaxing It - Piryani, Rano Mal; Piryani, Suneel; Piryani, Shomeeta; Shakya, Dhana Ratna; Huq, Muzaherul (Journal of Lumbini Medical College, 2020)
Cambridge Dictionary defines ‘lockdown’ as a situation in which people are not allowed to enter or leave a building or area freely because of an emergency. Merriam-Webster outlines three definitions of lockdown: a) the confinement of prisoners to their cell for all or most of the day as a temporary security measure, b) an emergency condition in which people are temporarily prevented from entering or leaving a restricted area during a threat of danger and c) a temporary condition imposed by governmental authorities as during the outbreak of an epidemic disease in which people are required to stay at their homes and refrain from or limit activities outside the home involving public contact. Our focus, here, is on lockdown strategy adopted to contain corona virus disease 2019 (COVID-19) pandemic.